Solve by graphing.
1 Answer | Add Yours
Equating both expressions of 2x yields:
-y + 1 = 5 + y
You need to isolate y variable to the left side such that:
-y - y = 5 - 1
-2y = 4 => y = -2 = -2
Plugging y in the first equation yields:
2x = -(-2) + 1 => 2x = 3 => x = `3/2`
The solution to the system of equations is the point of intersection of the lines 2x = -y+1; 2x = 5+y.
The coordinates of the point of intersection: (`3/2` ; -2).
Join to answer this question
Join a community of thousands of dedicated teachers and students.Join eNotes